A Novel Multiple Session Payment System - Harum, Norharyati; Ali, Mohanad Faeq; Abu, Nor Azman (Science and Information, 2018)
A wireless smartphone can be designed to process a financial payment efficiently.A user can just swipe his/her credit/debit card over the counter and all the processing needed shall be done seamlessly.A smartphone is a popular device to carry around.It is a hassle to carry and keep track on so many physical debit/credit cards in a wallet.An electronic debit/credit card on a smartphone is a more convenient alternative.This research project will embark on an electronic debit/credit card on a smartphone and migrate to an IoT money.A novel session payment system using IoT money has been introduced to minimise debit/credit card risk.The scope of this paper is confined to the security model for an easy payment system based on Internet of Things (IoT). Previously,each IoT money is unique and used once only on one-time payment.The session payment system will ease the burden on protecting the database of the payment system. This paper will extend the use of one-time payment to a multiple session payment system using an IoT money note.